Competitiveness of Bulgarian Economy in the Period 2003-2008 - Mishev, Georgi (Research Papers, 2010)
The study paper presents particular evaluation scores characterizing the competitiveness of Bulgarian economy in the period 2003-2008. The characteristics of the competitiveness are considered at two levels – national and firm-level. The source of empirical data for estimating the suggested scores is a regular survey of business environment conducted annually in Bulgaria during this period. The emphasis is put on some particular characteristics of the business environment related to the competitiveness of Bulgarian economy. Specific indicators are analyzed which directly or indirectly characterize the level of competitiveness. The assessment of the competitiveness characteristics is realized using the method of normalized evaluation score suggested by the author.